Conhecimento e atitude sobre o grau de incapacidade física na hanseníase: estudo de intervenção na atenção básica de saúde - Santana, Emanuelle Malzac Freire de (2021)
Leprosy is a disease with a high disabling power, whose evaluation by health professionals requires adequate knowledge and attitudes. Objectives: To test the content validity of an instrument creat to assess the knowledge and attitude of doctors and nurses in primary health care about the assessment of the degree of physical disability in leprosy; to analyze the effects of an educational intervention in the light of the Theory of Meaningful Learning on the knowledge and attitude of doctors and nurses in primary health care in the assessment of the degree of physical disability in leprosy; to compare the adequacy of the knowledge and attitude of doctors and nurses in primary health care in the assessment of the degree of physical disability in leprosy before and after educational intervention and; to associate the experiences in training and assistance to people with leprosy with the adequacy of knowledge and of attitude. Method: Research with two methods, methodological study for construction and validation of the instrument "Knowledge and Attitude on the Assessment of the Degree of Physical Disability in Leprosy", and intervention study, based on a training course with 122 professionals of primary health care from João Pessoa, Paraíba. Descriptive and inferential statistics techniques were applied, with a 5% significance level. The study was approved by the Research Ethics Committee CAAE: 10319319.5.0000.5188. Results: The instrument had an excellent Content Validity Index (CVI> 0.90) and Kappa (K = 1.00). After the intervention, there was an increase in the scores of all items of the instrument, with statistical significance in 20 of the 32 items (p <0.05). More than 85% of the professionals stated that they felt capable of conducting the evaluation steps, with an emphasis on anamnesis, palpation of the peripheral nerves, sensory and motor evaluation (p <0.001). The correctness averages were higher than 90%, changing the classification of the participants from inadequate to adequate. Conclusion: The instrument had excellent content validity, the educational intervention improved the knowledge and attitude of doctors and nurses in the assessment of the degree of physical disability in leprosy and the adequacy of the constructs was evidenced after the intervention for almost all of the participants. La lepra es una enfermedad con un alto poder invalidante, cuya evaluación por parte de los profesionales de la salud requiere de conocimientos y actitudes adecuados. Objetivos: Probar la validez de contenido de un instrumento construido para evaluar el conocimiento y la actitud de médicos y enfermeras de la atención primaria de salud sobre la evaluación del grado de discapacidad física en la lepra; analizar los efectos de una intervención educativa a la luz de la Teoría del Aprendizaje Significativo sobre el conocimiento y la actitud de los médicos y enfermeras de la atención primaria de salud en la evaluación del grado de discapacidad física en la lepra; comparar la adecuación de los conocimientos y la actitud de los médicos y enfermeras de la atención primaria de salud en la evaluación del grado de discapacidad física en la lepra antes y después de la intervención educativa; y asociar las experiencias en la formación y asistencia a las personas con lepra con la adecuación de los conocimientos y de actitud. Método: Investigación con dos métodos, estudio metodológico para la construcción y validación del instrumento “Conocimientos y Actitudes en la Evaluación del Grado de Discapacidad Física en Lepra”, y un estudio de intervención, basado en un curso de capacitación con 122 profesionales en la atención primaria de salud de João Pessoa,Paraíba. Se aplicaron técnicas estadísticas descriptivas e inferenciales, con un nivel de significancia del 5%. El proyecto fue aprobado por el comité de ética en investigación CAAE: 10319319.5.0000.5188. Resultados: El instrumento tuvo un excelente índice de validez de contenido (IVC> 0,90) y Kappa (K = 1,00). Después de la intervención, hubo un aumento en las puntuaciones de todos los ítems del instrumento, con significación estadística en 20 de los 32 ítems (p <0,05). Más del 85% de los profesionales manifestaron sentirse capaces de realizar los pasos de evaluación, con énfasis en anamnesis, palpación de nervios periféricos, evaluación sensorial y motora (p <0,001). Los promedios de aciertos fueron superiores al 90%, cambiando la clasificación de los participantes de inadecuada a adecuada. Conclusión: El instrumento tuvo excelente validez de contenido, la intervención educativa mejoró el conocimiento y actitud de médicos y enfermeras en la valoración del grado de discapacidad física en lepra y se evidenció la adecuación de los constructos luego de la intervención para casi todos los participantes.